Basic Profile of Child Marriage in Mauritania - Male, Chata; Wodon, Quentin (World Bank, Washington, DC, 2016)
Measures of child marriage are high in Mauritania. The share of women ages 18-22 who married as children is 35.2 percent, but it has declined over time. The share of girls marrying very early, before the age of 15, has also declined. Child marriage is associated with lower wealth, lower education levels, and higher labor force participation. These are however only correlations, not necessarily causal effects. In order to design programs and policies to reduce child marriage, information is needed on the trend in the practice over time, where it is most prevalent in a country, and what the characteristics of girls marrying early are.